How to Choose VLSI IC from E-Commerce Sites?: Sentiment Analysis with the help of Python Tools - Biswajit Biswas; Dr. Tuhin Mukherjee, (Indian Journal of Artificial Intelligence and Neural Networking (IJAINN), 2023)
Very Large Scale Integration (VLSI) dominates the digital technology in the present era. The VLSI based products have strong computing power in one hand & small in physical dimension due to its space minimization feature. Unfortunately, the people who use these ICs frequently are still not in a position to frequently purchase such VLSI IC in online mode & rely more on offline shopping from electronics shop in his or her locality. Due to the emergence of cashless economy, there is a paradigm shift in purchasing behavior of customers across the globe but it is an established fact that the ecommerce sites are still not matured for VLSI IC. This study is an attempt to use Natural Language Processing Tool Kit (NLTK) in Python & augment it with Valence Aware Dictionary and Sentiment Reasoner (VADER) analysis for development of a newly proposed App supposed to be used in the smart mobile phones for Sentiment Analysis of online feedbacks & reviews of customers who use VLSI IC frequently in their profession. The purpose is to create a confidence & prepare a convenient platform for those people towards their online purchasing behavior of VLSI IC. Uniqueness of this research is the use of word cloud for the textual review along with the star rating in the sentiment analysis through an automated system which is supposed to accept the Uniform Resource Locator (URL) of the concerned product only. The study demonstrates the validation on a set of specific product reviews from the amazon.in. & unfold the challenge of said App development successfully. The newly developed tools will be helpful for a customer to select such a VLSI IC before purchase.